SAP Business Analytics: A Best Practices Guide for Implementing Business Analytics Using SAP - DuttaRoy, Sudipa (Apress L. P, 2016)
Focus on SAP business analytics business gains, key features, and implementation. The book includes example implementations of SAP business analytics, the challenges faced, and the solutions implemented. SAP Business Analytics explains both the strategy and technical implementation for gathering and analyzing all the information pertaining to an organization.Key features of the book are:A 360-degree view of an organization's data and the methods to gather and analyze that dataThe strategies that need to be in place to gather relevant data from disparate systemsDetails about the SAP business analytics suite of productsThe technical implementations used to gather data from disparate systems such as ERP and CRM Real business cases as examplesAnalytics is the driving force in today's business, be it healthcare, marketing, telecommunications, or retail and hence the most vital part of any organization's strategy. What You'll LearnGain an understanding of business analytics in generalAbsorb the technical details of the SAP business analytics suite of productsDiscover the challenges faced during an enterprise-level analytics project implementationLearn the key points to be kept in mind during the technical implementation of an SAP business analytics projectWho This Book Is ForAnalytics strategists, BI managers, BI architects, business analysts, and BI developers.